2021
DOI: 10.1080/07481187.2021.1974666
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for dysfunctional grief and functional impairment for all causes of death during the COVID-19 pandemic: The mediating role of meaning

Abstract: The COVID-19 pandemic, coupled with significant social changes due to legislative and public health requirements, has changed the way in which people experience grief. We examined whether dysfunctional grief symptoms, disrupted meaning, risk factors, and functional impairment differed between people bereaved from COVID-19 and from other natural or violent causes in this same period. A sample of 409 participants (67.73% male; M = 37.54 years) completed an online survey in June 2021. There were no statistically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 36 publications
5
62
4
2
Order By: Relevance
“…Restricted funeral and memorialisation practices, inability to support one another and mourn collectively also made it difficult to find closure and begin to grieve (Torrens-Burton et al, 2021). These grief difficulties are consistent with the quantitative findings of a US pandemic study, that 'disrupted meaning' contributed to worse grief outcomes, and that higher levels of functional impairment occurred for all deaths during Covid19 compared with pre-pandemic times (Menzies et al, 2020;Breen et al, 2021).…”
Section: /Continued…supporting
confidence: 84%
“…Restricted funeral and memorialisation practices, inability to support one another and mourn collectively also made it difficult to find closure and begin to grieve (Torrens-Burton et al, 2021). These grief difficulties are consistent with the quantitative findings of a US pandemic study, that 'disrupted meaning' contributed to worse grief outcomes, and that higher levels of functional impairment occurred for all deaths during Covid19 compared with pre-pandemic times (Menzies et al, 2020;Breen et al, 2021).…”
Section: /Continued…supporting
confidence: 84%
“…Another study observed higher levels of functional impairment for all deaths during COVID-19 compared to pre-pandemic times, but no differences between COVID-19 and other types of deaths. 12 Quantitative and qualitative studies have identified difficult experiences of end-of-life care, such as lack of communication and contact with healthcare staff and patients prior to the death. 1 , 13 16 Where bereaved people struggled to make sense of such experiences, ‘disrupted meaning’ was found to cause functional impairment and dysfunctional grief symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…The higher levels of grief observed in this sample compared with pre-pandemic studies may be due to stressors universally experienced during the pandemic rather than specific to COVID-19 bereavements, including disruptions to the meaning-making process following a death (Breen et al ., 2021b). (Eisma and Tamminga, 2020) found that people in the Netherlands who recently experienced a non-COVID-19 death during the pandemic reported higher levels of acute grief than those recently bereaved before the pandemic.…”
Section: Discussionmentioning
confidence: 93%
“…(Eisma and Tamminga, 2020) found that people in the Netherlands who recently experienced a non-COVID-19 death during the pandemic reported higher levels of acute grief than those recently bereaved before the pandemic. (Breen et al ., 2021b) found that among people bereaved during the COVID-19 pandemic in the USA (N=409), there were no statistically significant differences in grief outcomes or functional impairment according to cause of death. Further research is required to establish which experiences and symptomatology are specific to the COVID-19 bereaved and which apply to the broader population of people bereaved during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation